The Effect of Palm Sugar Water Provisions on The Fitness of Futsal Players - Elly Septika; Lamri Lamri; Kurniati Dwi Utami (Universitas Negeri Semarang, 2025)
The provision of carbohydrate drinks during exercise helps to improve fitness, quench thirst, and accelerate rehydration and re-energisation of the body. Athletes require higher amounts of energy than non-athletes. Based on the results of observations before the intervention (Pre-Test), the fitness level of futsal players at SMK Negeri 1 Samarinda, five respondents fell into the category of very little, and four respondents fell into the category of less. This study aims to determine the effect of giving palm sugar water on the fitness of futsal players at SMK Negeri 1 Samarinda. The research design used is a one-group pretest-posttest design with 22 male students who are members of the futsal extracurricular. This research was conducted in the futsal field of SMK Negeri 1 Samarinda in August 2024 for 3 weeks, 8 times, and data analysis using a paired T-test. The results of this study indicate that the administration of palm sugar water significantly affects fitness, P = 0.001 (<0.05). After giving palm sugar water to the fitness level of futsal players at SMK Negeri 1 Samarinda, there is a significant effect.